Development of a specially designed drill bit for down-the-hole air hammer to reduce dust production in the drilling process. (20th January 2016) - Luo, Yongjiang; Peng, Jianming; Li, Lijia; He, Jiangfu; Gan, Xin; Yin, Kun; Zhao, Zhiqiang
Abstract: A specially structured drill bit is designed for a reverse circulation down-the-hole air hammer to reduce dust production in the local vicinity of the drilling site during operation. Computational fluid dynamics and experimental studies were conducted. Results show that the spray velocity of suction nozzles has an important effect on the performance of the drill bit for dust control. Three optimized drill bits were built for a GQ-89 reverse circulation down-the-hole air hammer and field-tested by drilling vertically downward boreholes in Xiao Qinling gold ore district. These drill bits have two mid-pressure restoring grooves with a diameter of 8 mm, two symmetrically placed flushing nozzles with diameter of 3 mm, and six uniformly distributed suction nozzles with diameter of 6 mm for each layer. Field tests show that employing the reverse circulation down-the-hole air hammer with specially designed drill bit has good dust control performance in the drilling processes. The specially designed drill bit can provide dust control efficiency of up to 99% with no need for additional sealing device, which is higher than both wet drilling and dry drilling by closing the drilling area. And employing reverse circulation down-the-hole air hammer with the current designed drill bit can efficiently protect drilling workers and equipment from threats of drilling dust. The usage of the specially designed drill bit has also significantly simplified the dust control apparatus for down-the-hole air hammer drilling method. Highlights: A special structure drill bit for reverse circulation DTH air hammer is designed. Orthogonal experimental design was used to optimize the parameter of the drill bit. Experimental results verified the CFD approach is capable for our simulation. Parameters of the suction nozzles are key parameters for the suction capacity. Using modified drill bit can obtain a clean working environment for drilling workers.